A time-resolved immunoassay to measure serum antibodies to the rotavirus VP6 capsid protein - Kavanagh, Owen (Elsevier/North-Holland Biomedical Press, 2013)
The rotavirus (RV) inner capsid protein VP6 is widely used to evaluate immune response during natural infection and in vaccine studies. Recombinant VP6 from the most prevalent circulating rotavirus strains in each subgroup (SG) identified in a birth cohort of children in southern India [SGII (G1P[8]) and SGI (G10P[11])] were produced. The purified proteins were used to measure VP6-specific antibodies in a Dissociation-Enhanced Lanthanide Fluorometric Immunoassay (DELFIA). The ability of the assay to detect a ≥2 fold rise in IgG level in a panel of serum samples from a longitudinal study was compared to a gold standard virus-capture ELISA. A strong association was observed between the assays (p < 0.001; chi-squared test) with assay performances remaining similar when the samples were subdivided as having a fold change increase in VP6 antibody levels (a) within 90 days of RV RNA detection in stool or (b) if no RV RNA was detected within that time period. This study demonstrates the suitability of using recombinant proteins to measure anti-RV immune responses and serves as a “proof of principle” to examine the antibody responses generated to other recombinant RV proteins and thereby possibly identify a correlate of protection.